Microbial metabolomics in open microscale platforms - Layla J. Barkal (Nature Portfolio, 2016)
Traditional methods for microbial culture and subsequent metabolomics are time-consuming and labour-intensive. Here the authors present a microscale culture platform with integrated extraction for efficient, low-volume metabolomics of relevant microenvironments and microbial co-cultures.